2007
DOI: 10.1038/sj.leu.2404762
|View full text |Cite
|
Sign up to set email alerts
|

The ρ-kinase inhibitors Y-27632 and fasudil act synergistically with imatinib to inhibit the expansion of ex vivo CD34+ CML progenitor cells

Abstract: Evidence from cell line-based studies indicates that q-kinase may play a role in the leukaemic transformation of human cells mediated by the BCR/ABL tyrosine kinase, manifest clinically as chronic myeloid leukaemia (CML). We therefore employed two separate inhibitors, Y-27632 and fasudil, to inhibit the activity of q-kinase against ex vivo CD34 þ cells collected from patients with CML. We compared the effects of q-kinase inhibition in those cells with the effects of direct inhibition of BCR/ABL using the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Even though our data in additional primary AML donors are limited in number, they are well in line with data generated by other groups in CML. 23,42 Interestingly, both our data and 1 of the earlier reports in CML suggest that normal HSPCs are less sensitive to ROCK1 inhibition than leukemic blasts. These observations and the excellent tolerability of prolonged fasudil exposure in humans 43,44 and in our mouse model argue for the feasibility of repetitive dosing to increase peak serum levels observed after a single application of this drug 25 to levels needed for efficient ROCK1 inhibition in vivo.…”
Section: Discussionsupporting
confidence: 68%
“…Even though our data in additional primary AML donors are limited in number, they are well in line with data generated by other groups in CML. 23,42 Interestingly, both our data and 1 of the earlier reports in CML suggest that normal HSPCs are less sensitive to ROCK1 inhibition than leukemic blasts. These observations and the excellent tolerability of prolonged fasudil exposure in humans 43,44 and in our mouse model argue for the feasibility of repetitive dosing to increase peak serum levels observed after a single application of this drug 25 to levels needed for efficient ROCK1 inhibition in vivo.…”
Section: Discussionsupporting
confidence: 68%
“…A publication by Burthem and colleagues shows that ROCK inhibitors such as Y-27632 and fasudil combined with the TKI imatinib synergistically inhibits the activity of human leukemic cells [26]. These results show that ROCK may be a potential additional therapeutic target in impairing the oncogenic activity of TK-driven malignancies and validate the use of these inhibitors as either single agents or combined with other TKIs as a possible therapeutic strategy.…”
Section: Discussionmentioning
confidence: 80%
“…Although most patients respond to first-line imatinib therapy, resistance (Volpe et al, 2009;Nair et al, 2012), toxicity (Faber et al, 2006) or intolerance has caused some patients to fail to respond to the standard dose. Thus, to optimize therapeutic benefit, physicians choose customized therapy based on each patient's historical response, adverse-event tolerance level, risk factors and the administration of anti-cancer herbal agents with low toxicity, which are attractive either alone or in combination with imatinib (Radujkovic et al, 2006;Walz and Sattler, 2006;Burthem et al, 2007;Murray-Rust and Rzepa, 2011;Agarwal et al, 2012). Shishodia et al reported that curcumin (isolated from the rhizome of the plant Curcuma longa) inhibited proliferation of primary CML cells and down-regulated STAT5 mRNA levels and activity (Shishodia et al, 2007).…”
Section: Discussionmentioning
confidence: 99%